Internet economics - McKnight, Lee W.; Bailey, Joseph P. (MIT Press, 1998)
The Internet has rapidly become an important element of the economic system. The lack of accepted metrics for economic analysis of Internet transactions is therefore increasingly problematic. This book, one of the first to bring together research on Internet engineering and economics, attempts to establish such metrics. The chapters, which developed out of a 1995 workshop held at MIT, include architectural models and analyses of Internet usage, as well as alternative pricing policies.